2015
DOI: 10.1016/j.fuel.2014.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Dual fuel diesel combustion with an E85 ethanol/gasoline blend

Abstract: In this experimental study, the ethanol/gasoline blend E85 was used as the primary fuel in a dual-fuel combustion concept. The E85 blend was injected at low pressure into the intake manifold and the mixture was ignited via a diesel fuel injection near top dead centre. The research engine was based on a heavy-duty diesel engine equipped with a common-rail injection system. Only the duration of the diesel injection was modified in the diesel injection system during the tests-the other diesel injection parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
1
35
0
2
Order By: Relevance
“…Taking into account this statement, it is clear that the low reactivity fuel characteristics and its amount in the blend have a significant contribution to the incylinder reactivity, and therefore, to the combustion development and its emissions. In this sense, recent works investigated the use of E85 fuel as alternative of gasoline on RCCI concept [24][25] [26] [27]. In terms of emissions, the use of E85 resulted in increased HC and CO levels with decreased NOx.…”
Section: Experimental and Numerical Studies Demonstrated That Reactivmentioning
confidence: 99%
“…Taking into account this statement, it is clear that the low reactivity fuel characteristics and its amount in the blend have a significant contribution to the incylinder reactivity, and therefore, to the combustion development and its emissions. In this sense, recent works investigated the use of E85 fuel as alternative of gasoline on RCCI concept [24][25] [26] [27]. In terms of emissions, the use of E85 resulted in increased HC and CO levels with decreased NOx.…”
Section: Experimental and Numerical Studies Demonstrated That Reactivmentioning
confidence: 99%
“…To this end, engine research and development groups have been trying for decades to better understand and describe the fundamentals of these processes, including alternative fuels and combustion strategies [2] [3]. Both experimental and computational approaches have brought important insight towards enhancing our understanding of the global and local processes governing fuel mixing and combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that dual-fuel PCI combustion with ethanol premixed, ultra-low soot and NOx emissions can be realized with nearly 60% indicated thermal efficiency [9]- [14]. It is also found that dual fuel engines are often observed with large cyclic variations.…”
Section: Introductionmentioning
confidence: 99%